Bat Rabies - Banyard, Ashley C. (Rabies, 2013)
The lyssaviruses are a diverse group of viruses capable of causing rabies, which is an invariably fatal encephalitic disease in both humans and animals. Currently, the lyssavirus genus consists of 12 species with 11 of these distinct species having been isolated from bats. The basis for the apparent geographical segregation of bat lyssavirus infection between the Old and New World is poorly understood. In the New World species of insectivorous, frugivorous, and hematophagous bats, all represent important reservoirs of rabies virus. In contrast, rabies virus has never been detected in Old World bat populations, despite being endemic in terrestrial mammals. Instead, both insectivorous and frugivorous bat species across the Old World appear to act as reservoirs for the non-rabies lyssaviruses. In this chapter, we describe the association of the different lyssaviruses with different bat species across the world, classifying bat species by their feeding behavior.